DOI: 10.33915/etd.2897
|View full text |Cite
|
Sign up to set email alerts
|

Levels of lateral flange bending in straight, skewed and curved steel I -girder bridges during deck placement

Abstract: Major-axis bending moment (Eqs. 1-1, 2-11) M + : Maximum moment in-between the cross-frame spacing (Grubb, 1991) M fw : Maximum fixed-end moment at the cross-frame locations (Grubb, 1991) M l : Lateral flange moment (Eq. 2-4) M lat : Lateral flange bending moment (Eq. 1-1) M nb : Maximum normal bending moment (Eq. 2-2) MPC: Multi-point constraint M u : Maximum moment capacity of the flange (Eq. 2-4) Mu: Factored major-axis bending M w : Maximum lateral moment in the bottom flange due to factored wind loading

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A multilinear relationship (Galindez, 2009) was used to represent the stress-strain characteristics used in the material modeling. This material model is shown in Figure 5.1, and the expressions employed to compute the curve are listed in Table 5.1.…”
Section: Structural Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…A multilinear relationship (Galindez, 2009) was used to represent the stress-strain characteristics used in the material modeling. This material model is shown in Figure 5.1, and the expressions employed to compute the curve are listed in Table 5.1.…”
Section: Structural Steelmentioning
confidence: 99%
“…Results of this project demonstrate that the proposed system is an economically competitive alternative for the short-span bridge market. Girder Tests) ..................................................... C.2.2 Data from Experiments 3 and 4 (Noncomposite Girder Tests) ............................................... Element and Strain Compatibility Results .......................................... C.3.2 Constrained Finite Strip Analyses using CUFSM ................................................................... Table 2.1: Unit Weights (AASHTO, 2010).................................................................................... Table 2.2: Multiple Presence Factors (AASHTO, 2010) .............................................................. Table 2.3: Equation Legend (AASHTO, 2010 (Galindez, 2009) ............... Table 5. 2: Average Steel Plate Properties .................................................................................... Table 6.1: Web Slenderness Values for Parametric Matrix of Girders ........................................ Table 6.2: Example Girder Properties (PL 84" × 7/16") ............................................................ Table 6.3: Assessment of Improved Stability with SIP Formwork.............................................. Table 7.1: Interpolated Maximum Span Lengths ........................................................................ Table A.1: Integration Constants ("C" Values) Figure 1.…”
mentioning
confidence: 99%
“…The focus of the field test was to assess the structure's performance during the placement of the concrete deck. Previous studies (Galindez, 2009;Jackson, 2013) have shown that the AASHTO approximation for lateral flange bending can significantly overestimate these stresses during deck placement. However, these studies are largely analytical in nature.…”
Section: Assessment Of Construction Behaviormentioning
confidence: 97%
“…The appropriate elements, mesh densities, and other associated model parameters (boundary conditions, material definitions, etc.) were adapted from previous research to achieve accurate results (Galindez, 2009). Loads applied are representative of typical construction sequences, including overhangs, formwork, screed/rail, walkway, and the finishing machine.…”
Section: Finite Element Modeling Techniquesmentioning
confidence: 99%
“…al., 2005) Girders........................................................................................... Figure 4.4: Bridge Generated by Algorithm................................................................................. (Galindez, 2009) .................. 5.5: Simple Span FEA Results vs. AASHTO Approximation ............................................ Figure 5.6: Parallel vs. Staggered Orientation ............................................................................…”
Section: Acknowledgmentsmentioning
confidence: 99%